Histological expression of methionine adenosyl transferase (MAT) 2A as a post‐surgical prognostic surrogate in patients with hepatocellular carcinoma. Issue 5 (15th February 2018) - An, Jihyun; Na, Seong Kyun; Shim, Ju Hyun; Park, Yang Soon; Jun, Mi Jung; Lee, Joo Ho; Song, Gi‐Won; Lee, Hac Chu; Yu, Eunsil
Abstract : Background and Objectives: Deregulation of methionine adenosyltransferase (MAT) is involved in hepatocarcinogenesis. This study aimed to investigate the prognostic implications of the level of histological MAT1A and MAT2A in patients with resected hepatocellular carcinoma (HCC). Methods: A total of 210 patients with HCC who underwent curative resection between 2004 and 2011 were included. The levels of MAT proteins were immunohistochemically measured. Results: MAT1A and MAT2A were over‐expressed in 134 (63.8%) and 124 (59.1%) of the 210 tumor tissues, respectively. Up‐regulation of tumoral MAT1A was independently associated with male gender, and inversely related to tumors >5 cm (adjusted odds ratios [OR] 2.59, P  = 0.008, and OR 0.44, P  = 0.012, respectively). Enhanced MAT2A expression was significantly related to age ≥60 years and serum AFP >200 ng/mL (OR 0.51, P  = 0.030; and OR 2.65, P  = 0.003; respectively). Tumoral MAT2A over‐expression independently predicted an increased rate of recurrence within 1 year after hepatectomy (adjusted hazard ratio [HR] 2.45, P  = 0.012), but that was not the case for MAT1A expression (HR 0.90, P  = 0.744). High MAT2A was also an independent predictor of early recurrence (HR 2.54, P  = 0.034) in the subset of patients without microvascular invasion ( n  = 155). Conclusions: Over‐expression of MAT2A in HCC may be a useful biomarker for predicting and monitoring tumor recurrence, especially early after hepatic resection.